PENGARUH BUDAYA KERJA, BEBAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA PEGAWAI KONTRAK DI LINGKUNGAN UNIVERSITAS MATARAM - Suswanto, Dwi (Jurnal Magister Manajemen, 2017)
This research is aimed at determining the significant effect of work habit, work load, and compensasion on the work satisfaction of contract staffs in Mataram University. This research is associative causality study. The population of this research are 344 contract staffs working in the administration from which 185 samples were selected through proportionate stratified random sampling. The analysis were conducted with multiple linear regression. The research showed that 1) work habit had positive and significant effect on the work satisfaction, 2) work load had negative but not significant effect on the work satisfaction, 3) compensasion had positive and significant effect on the work satisfaction. The Recommendation given that to improve a work satisfaction can be done through improving the work habit and compensation. Improving the work habit includes work discipline and enhancing the sense of belonging to the organization through the appreciation the expertise as well as provide role in the work. The aspect of compensation, the amount of compensation and timeliness of the provision needs to be increase. The application of incentives periodically is also necessary. Aspects of the work load is necessary to develop the job characteristics so that the work load is not impressed light. Keywords: work habbit, work load, compensation, work satisfaction